Nursing Activities Score by assistance sites in Intensive Care Units - Claudia Maria Silva Cyrino; Magda Cristina Queiroz Dell'Acqua; Meire Cristina Novelli e Castro; Elaine Machado de Oliveira; Sérgio Deodato; Priscila Masquetto Vieira de Almeida (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To compare the Nursing Activities Score (NAS) between the Assistance Sites in an Intensive Care Unit. Method: Descriptive, retrospective study, carried out in the Intensive Care Unit of a teaching hospital. The patients were organized in Assistance Sites according to their clinical characteristics and the nursing team's composition was organized in accordance with the Nursing Activities Score (NAS). The confidence interval was set at p < 0.05. Results: the majority were male surgical patients with a mean age of 56.8 years. The postoperative care Site presented the greatest patient turnover. The overall average NAS was 71.7%. There was a difference in the nursing workload between the different Assistance Sites. The shorter length of stay and the nonsurvivors contributed to increasing the workload in the ICU. Conclusion: Comparing the NAS in the different Sites made it possible to organize the work process of the nursing team according to each group, contributing to patient safety.